Characterization of aortic endothelial dysfunction in ovariectomized allergic asthmatic mice - Shinichi Asano; Alexandra P. Crawford; Cameron C. Felty; Amanda S. Hatcher; Abigail R. Patterson; Marina Diioia; Dovenia S. Ponnoth (PLoS ONE, 2026)
Clinical observations suggest that sex hormones may have a role in female asthma-related cardiovascular diseases (CVD), however, the mechanism by which sex hormones may influence CVD in asthmatics is unknown. The goal of this study was to determine if ovariectomized (OVX) mice with asthma alter asthma severity biomarkers and vascular reactivity. Female C57/BL6 mice were assigned to 4 groups: 1) sham vehicle control (VC), 2) OVX VC, 3) sham asthma, and 4) OVX asthma. Asthmatic groups were sensitized with 30 μg ovalbumin suspended in Imject alum by i.p. injections followed by 5% ovalbumin in saline for aerosol challenges. Vehicle groups received an identical treatment without ovalbumin. In the lungs, the eosinophil population was significantly higher in OVX asthma mice than in sham asthma mice (58 ± 9 vs. 76 ± 5%). Similarly, the OVX asthma group had significantly higher plasma anti-IgE (8.98 ± 1.66 vs. 27.5 ± 2.07 ng/mL) and elevated cytokines in bronchoalveolar lavage fluids. Isometric tension experiments demonstrated that maximal acetylcholine-induced aortic relaxation was significantly reduced by approximately 24% in both asthmatic mice groups compared with respective vehicle control mice. Similarly, the nitric oxide component of Ach-induced relaxation was significantly reduced in both asthma groups, but there were no differences between sham and OVX asthmatic mice. Our data demonstrated that OVX asthmatic mice developed exacerbated allergic lung responses, and lung-initiated inflammation can extend to impair endothelial function in the aorta.